Review and Criticism of the Translation of the Abd al-Qāhir al -Jurjānī's Book and His Modern Perspectives on Literary Criticism - Zahra Khosravi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present article reviews and criticizes the Abd al-Qāhir al-Jurjānī's book and his modern perspectives on literary criticism, translated by Maryam Mosharraf. Having the subject comparative linguistics, the book addresses some views of Abd al-Qāhir al-Jurjānī, a Muslim scholar of the fifth century AH, and his linguistic perspectives are compared with the views of some contemporary Western linguists, such as Saussure, the leader of the Structuralism School, and Chomsky, the pioneer of the generative-transformational approach, and John Lyon. The present article first deals with the issue in the works of the great Muslim scholars, and then in the other part analyzes the translation of Abd al-Qāhir al-Jurjānī 's book and his modern views on literary criticism. These contents fall into two parts: form and structure analysis and content analysis.